Pengaruh Laba Akuntansi, Arus Kas Operasi, NPM, Dan ROE Terhadap Return Saham Pada Perusahaan Sektor Barang Konsumen Primer Di BEI Tahun 2020-2023 - Pemayun, Tjok Istri Trisna Tari; Susanti, Jeni; Jatiwardani, Dian (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The boycott of products supporting Israel resulted in a decline in the share prices of companies in the Consumer Non-Cyclical sector. This causes fluctuations in stock returns, thus having an impact on investor decision making. To convince investors when faced with macroeconomic phenomena, such as the unpredictable boycott phenomenon, companies must be able to convey good company performance in the hope that there will be a recovery and shares are still worth buying. Therefore, investors need to pay attention to factors to conduct fundamental analysis of company performance. These factors include Accounting Profit, Operating Cash Flow, NPM, and ROE. This study aims to examine the effect of Accounting Profit, Operating Cash Flow, NPM, and ROE on Stock Returns in Consumer Non-Cyclical Sector companies listed on the Indonesia Stock Exchange in 2020-2023. The type of research used in this study is quantitative research. The sampling method used is purposive sampling method. This study analyzes secondary data sourced from www.idx.co.id which is the official website of the Indonesia Stock Exchange with the research period 2020-2023. The data analysis technique uses multiple linear regression analysis. Hypothesis testing was carried out using IBM SPSS Statistic 26 software. The results of the study show that accounting profit and ROE have a positive and significant effect on stock return partially. This indicates that the size of accounting profit is able to circulate positive signals for investors about the company's capabilities and good prospects by issuers. The higher the ROE value of a company, the more it will be able to increase the return on shares in companies in the primary consumer goods sector listed on the Indonesia Stock Exchange for the 2020-2023 period. Meanwhile, operating cash flow and NPM did not have a significant influence on the stock return partially. This is related to the phenomenon of boycotting Israeli-affiliated products in primary consumer goods sector companies in 2023. Simultaneously, accounting profit, operating cash flow, NPM, and ROE have a significant effect on return on shares.